Accounting Policies, Management Judgements And Financial Reporting Quality Of Small And Medium Enterprises In Nigeria: A Survey - Nangih, Efeeloo; Wali, Samuel Chikwuchehia; Anyanwu, Peggy Oluchi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
The accounting policy adopted by an enterprise, together with the level of approximations done by the management in financial statements, could either enhance or impair their relevance and reliability, and by extension, the credibility of financial decisions made by users of such reports. This is because financial statements portray the financial position and performance of entities. This study assesses the influence of management’s choice of accounting policy and accounting approximations in financial statements on the quality of financial reports of Small and Medium Enterprises in Nigeria. The study was anchored on the Stakeholders’ theory. The study also adopted the survey design approach. Data were mainly collected through the questionnaire and was analyzed using descriptive statistics and regression techniques. Findings revealed that wrong approximations may affect the quality of financial reports, together with other factors. It was recommended that management of small and medium enterprises should adhere to the provisions of accounting standards when designing their accounting policies and in their judgements/approximations; in order to reduce material errors and enhance the quality of their financial report.